Approaches to Multimodality Monitoring in Pediatric Traumatic Brain Injury - Appavu, Brian; Burrows, Brian T.; Foldes, Stephen; Adelson, P. David (Frontiers in Neurology, 2019)
Traumatic brain injury is a leading cause of morbidity and mortality in children. Improved methods of monitoring real-time cerebral physiology is needed to better understand when secondary brain injury develops and what treatment strategies may alleviate or prevent such injury. In this review, we discuss emerging technologies that exist to better understand intracranial pressure, cerebral blood flow, metabolism, oxygenation and electrical activity. We also discuss approaches to integrating these data as part of a multimodality monitoring strategy to improve overall patient care.